THE EFFECT OF E-SERVQUAL AND E-TRUST TOWARDS CUSTOMER SATISFACTION ON TIKTOK SHOP IN MANADO - Kotambunan, Tabita Olivia; Kindangen, Paulus; Gunawan, Emilia Margareth (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
The rapid growth of E-Commerce makes customer satisfaction a crucial factor in the increasingly fierce market competition.  In the world of e-commerce, customer satisfaction should be a major concern because it is influenced by various factors. To assess the level of customer satisfaction, two important aspects that need to be considered are service quality and E-Trust, which play a major role in building loyalty and improving the online shopping experience. The purpose of this study was to determine the effect of E-Service Quality, and E-Trust on Customer Satisfaction at TikTok Shop in Manado. The research method used in this study is quantitative. The data analysis techniques used in this research is multiple linear regression analysis, using the IBM SPSS 30 statistical program. The result of this study stated that E-Service Quality (X1), and E-Trust (X2) have a positive and significant effect on Customer Satisfaction (Y) partially, and then simultaneously E-Service Quality (X1), and E-Trust (X2) have a positive significant effect on Customer Satisfaction (Y).   Keywords: E-Service Quality, E-Trust, Customer Satisfaction